Teaching Vocabulary To Young Learners Using Flashcard AT BA Aisyiyah Kadilangu In 2014/2015 Academic Year - Wardani, Nita Myla, Aryati Prasetyarini, S.Pd, M.Pd, Nur Hidayat, M.Pd (2015)
In general, this study aims (1) to describe the implementation of teaching vocabulary to young learners using flashcard at BA Aisyiyah Kadilangu and especially (a) the objective, (b) the materials and (c) teaching procedures, (2) to describe the students' response, (3) to describe the strength and weakness of teaching vocabulary using flashcard. The type of this research is descriptive qualitative research. The researcher collects the data by observing the teaching learning process, conducting interview with teacher and students, and analyzes documentation during teaching-learning process. The technique for analyzing data is data reduction, data display, and conclusion. The result of this research shows that: (1) the implementation of teaching vocabulary to young learners using flashcard at BA Aisyiyah Kadilangu consists of the objective of teaching vocabulary is to improve the students' vocabulary mastery. The textbook used is entitled "English with Fun" and the material is animals. There are three activities in teaching-learning process, such as: opening, learning activities, and closing (2) most of the students gave good responses. They enjoyed the teaching-learning process. They were very interested in the process of learning English. It is making the students active and confidence because they do a lot of activities by using flashcard (3) It facilitates the students to base vocabulary by memorizing the word by using real picture.